Multivariate analysis of set pieces at women and men 2021-22 UEFA Champions League - Trejo, A.; Correa, R.; Trujillo-Baameiro, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Set pieces (SP) are widely regarded as significant technical-tactical indicators of sport performance in football (Ugalde and Rodríguez, 2021), with studies indicating they contribute significantly, up to 40%, to the overall tally of goals scored (Mitrotasios et al., 2021). While there has been a rise in research focusing on these critical moments in women´s football matches, there remains a noticeable gender disparity in the analysis of performance indicators in team sports (Adán et al., 2020). Therefore, the aim of the present study was to analyze and compare women´s and men´s offensive performance during direct and indirect free kicks (DFK; IFK) and corner kicks (CK) in the 2021-22 UEFA Champions League METHODS: The sample was composed of 1945 CK and free kick (FK) sanctioned at female and male 2021-22 UEFA Champions League (n=61 female matches and n=61 male matches). Observational methodology procedures were followed for collecting data. the binary regression and classification tree (Exhaustive CHAID) multivariate models were used to identify the best predictor variables for women and men. RESULTS: Results showed that 15,8 ± 3,9 SP were registered at the women´s tournament (6,0 ± 2,8 FK; 9,8 ± 3,1 CK) and 16,1 ± 4,8 SP at the men´s tournament (7,0 ± 3,2 FK; 9,2 ± 3,3 CK) having CK a significant relationship (p < 0.05) with women and FK (p